2018
DOI: 10.1159/000495235
|View full text |Cite
|
Sign up to set email alerts
|

Cytoskeleton Structure in Mouse Sperm and Testes After 30 Days of Hindlimb Unloading and 12 Hours of Recovery

Maria A. Usik,
Irina V. Ogneva

Abstract: Background/Aims: Changes in the external mechanical field result in cytoskeleton reorganization and the formation of adaptive patterns in different types of cells, including somatic cells and sex cells. The aim of this research was to study the protein and mRNA content of cytoskeletal and sperm-specific genes in the sperm and testis cells of mice. Methods: Mice were subjected to 30 days of antiorthostatic suspension to simulate weightlessness, followed by 12 h of recovery, while receiving essential phospholipi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
25
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(27 citation statements)
references
References 41 publications
2
25
0
Order By: Relevance
“…For sperm collection, we used both caudal epididymides from each male mouse and received sperm as described previously [ 10 ]. Briefly, immediately after extraction, the epididymis was placed in 1.2 mL α-MEM medium with 10% bovine serum heated to 37 °C.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…For sperm collection, we used both caudal epididymides from each male mouse and received sperm as described previously [ 10 ]. Briefly, immediately after extraction, the epididymis was placed in 1.2 mL α-MEM medium with 10% bovine serum heated to 37 °C.…”
Section: Methodsmentioning
confidence: 99%
“…After a 30-day antiorthostatic suspension of mice, we observed various changes in the spermogram of the mice: a decrease in the number of motile spermatozoa, a significant decrease in the proportion of viable sperm and a normal sperm morphology. According to the data on the sperm-specific protein levels, there was a shift towards immature forms, as well as various changes in the content of cytoskeletal proteins and the expression of the corresponding genes [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, in mammals, the speed of sperm movement decreased. This result has been shown in experiments with animals that underwent antiorthostatic suspension [ 22 , 38 ] and during exposure of isolated sperm of humans and mice to simulated microgravity conditions [ 39 , 40 ].…”
Section: Discussionmentioning
confidence: 54%
“…We previously suggested that cell mechanoreception can be realized through deformation of the membrane and cortical cytoskeleton, leading to the initiation of various signaling pathways with increases and decreases in external mechanical stress [ 41 , 42 ]. Moreover, a change in the lipid composition of membranes and a decrease in cholesterol, which leads to rearrangements of the cortical cytoskeleton and an increase in the resistance of these structures to deformations, allowed us to prevent the effects of simulated microgravity in various cases, including for mouse sperm [ 22 , 43 ]. However, in this study, even with the use of essential phospholipids, the increased linear speed of the tail of the sperm of the fruit fly was maintained, although it was not as pronounced.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation